PERAN BAHASA DALAM PENGUATAN KARAKTER SISWA KELAS II SD ISLAM GUPPI KOTA SORONG - Ekawati, Santi; Ismayanti, Mutmainnah; Styawati, Kukuh Arif; Arsyad, Alifah Junayani; Buwana, Santika; Handayani, Sulis; Khoiri, Abdul Aziz (Universitas Negeri Semarang, 2025)
The aim of this research is the role of language in strengthening the character of class II students at Guppi Islamic Elementary School, Sorong City. The research method used in this research is a qualitative method with a descriptive approach. Data collection techniques in this research are observation, interviews and literature study. Data analysis techniques in this research include data collection, data display, data reduction, and drawing conclusions. The results of the research show that 1) The role of language is proven to be very significant in forming the character of class II students at GUPPI Islamic Elementary School, Sorong City. The use of polite and structured language in learning not only improves students' communication skills, but also forms better personalities, 2) 2. The school's efforts to optimize the role of language have been carried out systematically through various programs such as